2008
DOI: 10.1096/fj.08-109348
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variants of streptokinase fromStreptococcus pyogenesdisplay functional differences in plasminogen activation

Abstract: A common mammalian defence mechanism employed to prevent systemic dissemination of invasive bacteria involves occlusion of local microvasculature and encapsulation of bacteria within fibrin networks. Acquisition of plasmin activity at the bacterial cell surface circumvents this defence mechanism allowing invasive disease initiation. To facilitate this process, S. pyogenes secrete streptokinase, a plasminogen activating protein.Streptokinase polymorphism exhibited by S. pyogenes isolates is well characterised. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(97 citation statements)
references
References 44 publications
5
91
1
Order By: Relevance
“…Genes with a differential presence or absence among tissue-tropic strains include cpa (encoding a type I collagen binding protein) (168), prtF1 (encoding the fibronectin binding protein PrtF1) (169), sof (encoding serum opacity factor, which contains a fibronectin binding domain) (170,171), and prtF2 (encoding the fibronectin binding protein PrtF2) (172). Loci that form discrete phylogenetic lineages, which can then be associated with tissue-specific emm patterns, include the transcriptional regulators mga (a global regulator of numerous virulence factors) (173), rofA and nra (mutually exclusive transcriptional regulators of the genes in the FCT region) (167), and ska (encoding the plasminogen-activating protein streptokinase) (174,175). While it is conceivable that tissue site preferences for infection in the throat or skin might be explained by the expression and/or regulation of tissue-specific colonization factors such as adhesins, the exact mechanisms responsible for tissue tropism are yet to be fully elucidated.…”
Section: Gas Tissue Tropismmentioning
confidence: 99%
See 2 more Smart Citations
“…Genes with a differential presence or absence among tissue-tropic strains include cpa (encoding a type I collagen binding protein) (168), prtF1 (encoding the fibronectin binding protein PrtF1) (169), sof (encoding serum opacity factor, which contains a fibronectin binding domain) (170,171), and prtF2 (encoding the fibronectin binding protein PrtF2) (172). Loci that form discrete phylogenetic lineages, which can then be associated with tissue-specific emm patterns, include the transcriptional regulators mga (a global regulator of numerous virulence factors) (173), rofA and nra (mutually exclusive transcriptional regulators of the genes in the FCT region) (167), and ska (encoding the plasminogen-activating protein streptokinase) (174,175). While it is conceivable that tissue site preferences for infection in the throat or skin might be explained by the expression and/or regulation of tissue-specific colonization factors such as adhesins, the exact mechanisms responsible for tissue tropism are yet to be fully elucidated.…”
Section: Gas Tissue Tropismmentioning
confidence: 99%
“…Ska is a single-chain, 414-amino-acid protein composed of three distinct domains (333). Phylogenetic studies of the most divergent ska sequences have revealed two main sequence clusters (cluster types 1 and 2), with evidence of smaller subclusters observed in cluster type 2 sequences (cluster types 2a and 2b) (174,175). Ska variants display significant functional differences, with cluster type 2, but not type 1, streptokinase requiring fibrinogen to efficiently activate plasminogen (175).…”
Section: Subversion Of the Plasminogen Activation Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…This can hydrolyze fibrin and promote the spread of GAS through tissues. Streptokinase is an important virulence factor that acts in concert with plasmin(ogen)-binding proteins (Table 1), and the reader is referred to a recent article for further information (388).…”
Section: Virulence Factorsmentioning
confidence: 99%
“…Out of these nine genes, five were previously described for human S. dysgalactiae subsp. equisimilis: lbp (encoding the adhesion Lmb, a laminin-binding protein) (62), ska (encoding the plasminogen-activating Skastreptokinase A protein) (37), slo (encoding the cytolytic streptolysin O toxin) (54), emm (encoding the M protein), as well as scpA (encoding a C5a peptidase), with the latter two genes acting on the complement pathway of the host, inhibiting bacterial opsonization and phagocytosis (8,20). Both the lbp and scpA genes have been found in human GBS isolates and are usually absent in bovine GBS isolates (14).…”
mentioning
confidence: 99%